2015
DOI: 10.1038/srep16725
|View full text |Cite
|
Sign up to set email alerts
|

Tuftsin-derived T-peptide prevents cellular immunosuppression and improves survival rate in septic mice

Abstract: The primary mechanisms of sepsis induced cellular immunesuppression involve immune dysfunction of T lymphocytes and negative immunoregulation of regulatory T cells (Tregs). It has been found that tuftsin is an immune modulating peptide derived from IgG in spleen. T-peptide is one of tuftsin analogs. Herein, we examined the effect of T-peptide on cell-mediated immunity in the presence of lipopolysaccharide (LPS) and the survival rate in septic mice. T-peptide regulated the proliferative ability of CD4+CD25− T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 51 publications
(106 reference statements)
1
26
0
Order By: Relevance
“…We have reported that the percentage and stability of Tregs were higher in septic patients than those without sepsis; a reduction in the stability of Tregs was accompanied by an improvement in survival rate and immune dysfunction of T-lymphocytes with sepsis [1215, 23, 24]. Foxp- 3, which is still the mainly intracellular marker for identification of Tregs, was also critical for their function, differentiation, and maintenance [10, 11].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have reported that the percentage and stability of Tregs were higher in septic patients than those without sepsis; a reduction in the stability of Tregs was accompanied by an improvement in survival rate and immune dysfunction of T-lymphocytes with sepsis [1215, 23, 24]. Foxp- 3, which is still the mainly intracellular marker for identification of Tregs, was also critical for their function, differentiation, and maintenance [10, 11].…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + CD25 + Tregs and CD4 + CD25 − T cells were isolated using mouse CD4 + CD25 + Tregs isolation kits, which we have recounted [23, 24]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations